Limnological variables and nutritional content of submerged aquatic macrophytes in a tropical lagoon - Esteves,Bruno dos Santos (2010)
AIM: The aim of this study was to evaluate elemental composition (C, N and P) and carbohydrate and lipids content of aquatic macrophytes Egeria densa, Ceratophyllum demersum and Najas marina found in a lagoon of Norte Fluminense and relate these data to limnological parameters measured in the same period; METHODS: The samples were obtained from 10 sites throughout the lagoon in July/2001 (dry season) and January/2002 (rainy season) with determinations limnological parameters and quantification of nutrient content and biochemical composition of the aquatic macrophytes; RESULTS: High values of electrical conductivity and alkalinity explain the spatial distribution of the studied macrophytes; and the pH values (<9.0), O2 super-saturation and CO2 sub-saturation suggest a high primary production of both phytoplankton and submersed aquatic macrophytes. For nutrients assessed on aquatic macrophytes, significant seasonal variations were observed in total phosphorus content (p < 0.05), total nitrogen and total carbon, however, without a clear pattern between seasons and macrophytes There was a tendency to higher concentrations of P in the tissues of macrophytes in the rainy season, as well as carbohydrates and lipids, suggesting that this period presents better conditions to Ceratophyllum demersum and Egeria densa development in the Campelo Lagoon; CONCLUSIONS: There was no clear association between the nutrient content and reserves found in macrophytes with limnological and environmental parameters.